Influence of Various Factors on the Development of Karawo Traditional Textiles in Gorontalo Province, Indonesia - Hasdiana; Masayuki Sakakibara; Ni Kadek Karuni; I Wayan Sudana (Institut Seni Indonesia Denpasar, 2023)
This study aims to clarify the influence of various factors on the development of traditional textiles, by examining the case of the development of traditional karawo textiles in Gorontalo Province, Indonesia from 1970 to 2020. This study employs a qualitative research method with a historical approach. Data were collected through historical documents, observation, interviews, and a literature review. Data were analyzed interactively with continuous comparisons during and after data collection. The results showed that the development of traditional karawo textiles from 1970 to 2020 can be further divided into three distinct periods: 1970–2000, 2000–2010, and 2010–2020. During each period, karawo textiles were influenced by various factors, both internal and external. The most influential internal factors were the emergence of craftspeople and designers as production bases and continuous innovation. The most influential external factors were the actions of government and commercial institutions. Government policies encouraged individuals and non-governmental organizations to contribute to the development of karawo textiles. Commercial institution influent the distribution and marketing of karawo textile products. The study also describes the types of factors and their impacts. The study concludes that to ensure the sustainable development of traditional textiles, therefore those internal and external factors must consistently contribute from time to time.